On a Key Exchange Protocol - Barcau, Mugurel; Paşol, Vicenţiu; Pleşca, Cezar; Togan, Mihai (Innovative Security Solutions for Information Technology and Communications, 2017)
In this paper we investigate an instance of the generalized Diffie-Hellman key exchange protocol suggested by the equidistribution theorem. We prove its correctness and discuss the security. Experimental evidences for the theoretical results are also provided.